(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract Riding a bike is a great way for children to stay active and explore the world around them. However, safety concerns have become a growing issue for parents and guardians. This study aims to address this issue by developing a child safety bike with various safety features, including an IoT-based accident detection system, monitoring camera, GPS tracking device, and SMS notification. These safety features are designed to increase child safety while riding bikes by providing parents and guardians with real-time updates on their child’s location, any accidents or collisions, and live video footage. The prototype’s design, schematic diagram, and control system were implemented and analyzed. The accident detection system uses an accelerometer sensor to detect sudden changes in motion, and the GPS tracking device provides real-time location updates. The SMS notification system alerts parents or guardians if their child deviates from a predetermined route. However, if a child does not have an accident but presses the button for a false alarm/accident, the SMS alert will not be received by the guardians or parents. For monitoring, the FTDI adapter was used to connect the ESP32 module camera to capture images and live video footage of the rides and notify parents or guardians in real time. The researchers found that the technologies used, including the IoT-based accident detection system, monitoring camera, GPS tracking device, and SMS notification feature, were compatible with each other. The prototype was functional and successful, as confirmed by the positive feedback from the respondents regarding the efficiency, durability, safety, and economy of the prototype. The researchers concluded that the use of these technologies in the development of the prototype is effective in creating a child-safety bike. In summary, the development of a child safety bike with an IoT-based accident detection system, monitoring camera, GPS tracking device, and SMS notification is an innovative solution to the growing safety concerns of parents and guardians. The prototype developed in this study shows promising results in improving child safety during bike rides. This research contributes to the throwing field of IoT and promotes child safety in outdoor activities.